Construction of a Jejunal Pouch After Total Gastrectomy - Doussot, Alexandre (Medknow Publications & Media Pvt Ltd, 2014)
Total gastrectomy for cancer results in many digestive troubles leading to an impairement of the quality of life. Different types of reconstruction have been proposed to improve the postoperative digestive functions. According to several prospective randomized trials and a recent meta-analysis, the Roux-en-Y jejunal pouch construction appears to be the best technique for reconstruction concerning the postoperative quality of life. However, this safe reconstructive surgery is not still recognized as a gold standard.